.33(9-2x)=x+1

Simple and best practice solution for .33(9-2x)=x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .33(9-2x)=x+1 equation:


Simplifying
0.33(9 + -2x) = x + 1
(9 * 0.33 + -2x * 0.33) = x + 1
(2.97 + -0.66x) = x + 1

Reorder the terms:
2.97 + -0.66x = 1 + x

Solving
2.97 + -0.66x = 1 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
2.97 + -0.66x + -1x = 1 + x + -1x

Combine like terms: -0.66x + -1x = -1.66x
2.97 + -1.66x = 1 + x + -1x

Combine like terms: x + -1x = 0
2.97 + -1.66x = 1 + 0
2.97 + -1.66x = 1

Add '-2.97' to each side of the equation.
2.97 + -2.97 + -1.66x = 1 + -2.97

Combine like terms: 2.97 + -2.97 = 0.00
0.00 + -1.66x = 1 + -2.97
-1.66x = 1 + -2.97

Combine like terms: 1 + -2.97 = -1.97
-1.66x = -1.97

Divide each side by '-1.66'.
x = 1.186746988

Simplifying
x = 1.186746988

See similar equations:

| 36w+10+7w= | | 3(2-2)/2=-z | | w^4/5-16=0 | | 9-3(4-3r)+12r= | | -7/2v=-35 | | x^3-12x+16= | | 2.7÷4/3= | | 0.08(y-9)+0.18y=0.20y-0.9 | | .16666667(2x+4)=.083333(x-4) | | -2x=1x+3 | | 6/(x^5/11)=0 | | 2.7÷4/3 | | 7a+7b+7a+7b= | | -4y-11=8y+25 | | 5/6x=61/6 | | Cscydx+sec^2xdy=0 | | 6x+9=-99 | | 8z^2+14z+3=0 | | -11x+x=-7x-8(-x+1) | | 9x+15=9x+15 | | .04x-3.5=-.86 | | 9(x+15)=9x+135 | | .04-3.5=-.86 | | 2n+1=n^2-1 | | -1/3u-1/5=2/3u-3 | | 0=-x^2-4x+21 | | 5+(-8)8=29 | | b-1/2-a/3 | | -3(2n-5)=-3n+15 | | 2x/5=5 | | 7x+14=-2x-17 | | 7+2x-4=5x+8-2x |

Equations solver categories